RURAL FULL-TIME SCHOOL: FACING BARRIERS TO EDUCATIONAL QUALITY (Editora Impacto Científico, 2025)
The aim of this article is to analyze the main challenges faced in implementing full-time schools in rural areas in Brazil, considering the structural, pedagogical, logistical and political aspects that affect their implementation. The research is qualitative in nature, with an exploratory approach and a bibliographical basis, based on recent authors and studies that discuss rural education and public policies aimed at extended day schools. The results show that the full-time proposal, although potentially beneficial for the all-round development of students, encounters serious obstacles when transposed to the rural context. Among the obstacles identified are the precariousness of the school infrastructure, difficulties with transportation and food, the lack of specific teacher training, the mismatch between the curriculum and the local reality and the low level of community participation in educational management. In addition, the lack of public policies aimed at the countryside accentuates historical inequalities and compromises the effectiveness of full-time schools in rural areas. The discussion points out that simply extending school time does not guarantee better learning conditions, especially when it disregards the territorial and cultural diversity of rural communities. Successful experiences indicate that contextualized models, built with local participation and intersectoral support, can promote greater inclusion, permanence and educational quality. To be effective, full-time schools in rural areas need to be part of a political-pedagogical project committed to equity and to strengthening the links between education, territory and identity. The conclusion is that tackling the challenges of rural full-time schools requires continuous public investment, professional development, listening to communities and building educational policies that are sensitive to the realities of the countryside.